Traumatic Brain Injury—A Review of Intravenous Fluid Therapy - Pigott, Armi; Rudloff, Elke (Frontiers in Veterinary Science, 2021)
This manuscript will discuss how various fluid prescriptions can affect animals with traumatic brain injury (TBI). The effects of fluid osmolality and tonicity on cerebral blood flow and intracranial pressure in the patient with TBI will be discussed.